The Framework of Cooperative Problem-based Learning (Co-PBL) to Promote Verbal Creativity in EFL Writing: Is It Feasible? - M. Ali Ghufron; Siti Ermawati (JURNAL ARBITRER, 2018)
One of the influential factors that could affect students' writing skill is verbal creativity (VC). As an attempt to promote VC in EFL writing, two learning models i.e. cooperative learning and problem-based learning are incorporated and modified. This study was aimed at: (1) describing the structure of the framework of Co-PBL in order to promote VC in EFL writing; and (2) evaluating the feasibility of the framework of Co-PBL in EFL writing class. To achieve the goals of this study, a descriptive explanatory research was applied. It involves the EFL writing teachers and the first and second-grade students of English Education Department of a private university in East Java, Indonesia. The data were gathered through Focus Group Discussion (FGD), observation, semi-structured interview, and questionnaire. Incorporating cooperative learning (CL) and problem-based learning (PBL) results in the Co-PBL framework to guide the students through PBL cycles based on CL principles. The Co-PBL framework was also modified by inserting learning activities which could promote VC in EFL writing in each phase or cycle of PBL. Further, it was also confirmed that the Co-PBL framework is feasible to be implemented in EFL writing class. These findings, then, might have significant implications for EFL writing teachers and students.